Market access: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
This Executive Brief examines 2012-13 developments in ACP countries’ access to the EU market. The emergence of a range of differentiated market access arrangements (EPAs/Interim EPAs, the Everything But Arms Agreement and standard Generalised Systems of Preferences) has to be examined in the broader context of the EU’s evolving trade and development strategy, which includes also a number of new FTA agreements (e.g. Latin America, India). After analyzing the recent developments of EU-ACP market access measures and negotiations (including the increasing European emphasis on production process requirements for market access), the Brief presents a series of challenges that ACP governments will have to address in the near future. The Brief also presents insights on ACP access to non-EU countries, such as the US, China, India and Brazil.